The Sinophone roots of Javanese Nini Towong - CHAN, Margaret (Institutional Knowledge at Singapore Management University, 2017)
This article proposes that Nini Towong, a Javanese game involving a possessed doll, is an involution of fifth-century Chinese spirit-basket divination. The investigation is less concerned with originist theories than it is a discussion of the Chinese in Indonesia. The Chinese have been in Southeast Asia from at least as early as the Ming era, yet Chinese contributions to Indonesian culture is an understudied area. The problem begins with the asymmetrical privileging of Indic over Sinic influences in early European scholarship, a situation which in turn reveals the prejudices that the Europeans brought to bear in their dealings with the Chinese of Southeast Asia in the seventeenth to nineteenth century. Europeans introduced the Chinese-Jew analogy to the region. Their disdain contributed to indigenous hostility toward the Chinese. Racialism is a sensitive topic but a reminder of past injustices provides a timely warning in this moment of tense world geopolitics. © Nanzan University Anthropological Institute.